Productive packaging using innovative locking mechanism in die-cut technique / Irfan Zuhair Shaharudin - Shaharudin, Irfan Zuhair (Universiti Teknologi MARA, Perak, 2020)
Packaging design involves a process that includes design, evaluate, and produce a material used to protect a product. Simply put, good packaging is a paperboard cartons containers type are receptacles that hold, protect, and organize products. The case study focuses on producing suitable packaging for the product for the brand of Resepi Nani Rostam. This brand provides two different flavors of condiments; “Sambal Hijo Petir” and “Sambal Paru Letop”. Previously, the company uses plastic as its packaging. The revolutionized printed-packaging design facilitates the 2 in 1 campaign. Further improvement is made by applying an innovative die-cut technique in the packaging design. This technique enables the locking mechanism; which would ease the handling and packing of the product. Moreover, this newly designed packaging employs the use of augmented reality technology too. This technology gives a real subject, captured on video or camera, the technology that real-world images with extra layers of digital information. Hence, the improvements and innovation on the packaging will help products’ visibility, increase their growth, and market share. It will also offer a more cost-effective packaging solution and maintain sustainability through their shelf-life.